2020
DOI: 10.3389/fendo.2020.00126
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for a More Disrupted Immune-Endocrine Relation and Cortisol Immunologic Influences in the Context of Tuberculosis and Type 2 Diabetes Comorbidity

Abstract: Fernández et al. Immune-Endocrine Relation Tuberculosis Diabetes response to Mtb stimulation (increased IL-2 and IFN-γ production), even when exposed to inhibitory cortisol doses. TB+DM patients show a more unbalanced immuno-endocrine relationship, respect the non-diabetic counterparts, with a relative deficiency of cortisol immunomodulatory influences, despite their more favorable microenvironment for cortisol-mediated immune effects.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 101 publications
0
11
0
Order By: Relevance
“…The se h ormo nes may pro m ote immunosuppression during treatment, reducing the function of immune cells to work synergistically with antibiotics to clear mycobacteria from the lung. Santucci et al (2011) and Fernandez et al (2020) found lower leptin levels and higher cortisol levels in TB patients compared to controls, coinciding with higher inflammatory biomarkers, such as CRP, IL-6, and IL-1b (16,31). Furthermore, Santucci et al (2011) found leptin and cortisol changes to be more extreme in severe TB disease than in mild disease.…”
Section: Type 2 Diabetes Impacts Lung Immune-endocrine Interactions: ...mentioning
confidence: 93%
See 2 more Smart Citations
“…The se h ormo nes may pro m ote immunosuppression during treatment, reducing the function of immune cells to work synergistically with antibiotics to clear mycobacteria from the lung. Santucci et al (2011) and Fernandez et al (2020) found lower leptin levels and higher cortisol levels in TB patients compared to controls, coinciding with higher inflammatory biomarkers, such as CRP, IL-6, and IL-1b (16,31). Furthermore, Santucci et al (2011) found leptin and cortisol changes to be more extreme in severe TB disease than in mild disease.…”
Section: Type 2 Diabetes Impacts Lung Immune-endocrine Interactions: ...mentioning
confidence: 93%
“…Santucci et al (2011) and Fernandez et al (2020) found lower leptin levels and higher cortisol levels in TB patients compared to controls, coinciding with higher inflammatory biomarkers, such as CRP, IL-6, and IL-1β ( 16 , 31 ). Furthermore, Santucci et al (2011) found leptin and cortisol changes to be more extreme in severe TB disease than in mild disease.…”
Section: Type 2 Diabetes Impacts Lung Immune-endocrine Interactions: ...mentioning
confidence: 97%
See 1 more Smart Citation
“…DHEAS levels were lower in hepatitis C virus (HCV) coinfected HIV patients (Mauboussin et al 2004). Multiple studies have observed decreased DHEA and DHEAS in patients with tuberculosis (Santucci et al 2011;Fernandez et al 2020) and schistosoma infection intensity was lower in patients with high concentrations of DHEAS (Kurtis et al 2006).…”
Section: Infection and Immunitymentioning
confidence: 99%
“…Type 2 diabetes is one of the risk factors for dementia, which has a signi cant impairment on brain cognition since its early stage. 1,2 In recent years, the incidence of diabetes has increased year by year 3 , and many studies have shown that diabetes is an independent high risk factor for cognitive impairment. 4 The probability of cognitive impairment in patients with diabetes is signi cantly higher than that in ordinary people.…”
Section: Introductionmentioning
confidence: 99%